Indonesia’s Export-Import Analisys: Granger Causality Approach - Syaparuddin, Syaparuddin (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2017)
In a global economy context, the role of export-import becomes really important in supporting economic growth. An interesting phenomenon is that, most of Indonesian export are import-content and capital goods.This study is aimed at (1) analyzing Indonesia’s export-import patterns, (2) analyzing causality relationship between export and import in Indonesia. Analysis method used in this research is Granger Causality model. The result of study shows that the patters of the progress and the changes of Indonesia’s export and import have similar patters since 1980-2015. Those have causality relationship which indicate that export and import are mutual dependence. The conclusion of the research is that when Indonesia’s export would be increased so import should also be increased. On the other hand, the increasing of import must also be preceded by the increasing in export. JEL Classification: F13, F17, F18Keywords: Export, Important and Causality Granger